ERA-20C Project (ECMWF Atmospheric Reanalysis of the 20th Century) ... - European Centre For Medium-Range Weather Forecasts (UCAR/NCAR - Research Data Archive, 2014)
ERA-20C is ECMWF's first atmospheric reanalysis of the 20th century, from 1900-2010. It assimilates observations of surface pressure and surface marine winds only. It is an outcome of the ERA-CLIM project.ERA-20C was produced with IFS version CY38r1 and the same surface and atmospheric forcings as the final version of the atmospheric model integration ERA-20CM. A coupled atmosphere land surface and ocean wave model is used to reanalyze the weather, by assimilating surface observations. The ERA-20C products describe the spatial-temporal evolution of the atmosphere (on 91 vertical levels, between the surface and 0.01 hPa), the land-surface (on 4 soil layers), and the ocean waves (on 25 frequencies and 12 directions).The horizontal resolution is approximately 125 km (spectral truncation T159). Note that atmospheric data are not only available on the native 91 model levels, but also on 37 pressure levels (as in ERA-Interim), 16 potential temperature levels, and the 2 potential vorticity unit level. NCAR's Data ...